1966
DOI: 10.1002/j.1551-8833.1966.tb01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Control of Corrosion

Abstract: This article considers chemical control of corrosion as an alternative to a variety of consequences. It is most effective as a supplement to other protective measures. Because of the variety of water qualities and of environments, it is subject to many interesting complications. The application of chemical control may be limited by cost; its effectiveness may be limited by the nature of the distribution system. In the public water utilities, the range of measures for chemical control is limited by the undesira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…18 Similarly, Larson observed that there was a difference in the reactions taking place in the anode and cathode of the Fe surface with and without a buffer. 19 Table 4 summarizes the anodic and cathodic reactions for Fe corrosion of Larson's study. The anodic reaction under the presence of buffer is the oxidation of a ferrous ion that yields a weak acid, H 2 CO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…18 Similarly, Larson observed that there was a difference in the reactions taking place in the anode and cathode of the Fe surface with and without a buffer. 19 Table 4 summarizes the anodic and cathodic reactions for Fe corrosion of Larson's study. The anodic reaction under the presence of buffer is the oxidation of a ferrous ion that yields a weak acid, H 2 CO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Natural organic matter (NOM). Several studies (Lind Johansson, 1989;Sontheimer et al, 1981;Larson, 1966) found that NOM decreased the corrosion rate of both galvanized steel and cast iron. NOM was also found to encourage a more protective scale (Campbell & Turner, 1983) and alter the redox chemistry by reducing Fe +3 colloids to soluble fer-rous iron (Deng & Stumm, 1994).…”
Section: Other Compounds Have Effectsmentioning
confidence: 99%
“…Organic matter: Large organic molecules can reduce iron corrosion rates by accumulating and coating the pipe network surfaces over time. The combination of organic and inorganic matter also assists in forming a stronger protective layer [ 29 ]. Yet, organic matter can alter the redox potential of the reaction system, thereby increasing the concentration of soluble ferrous iron in water.…”
Section: Stability Of Water Quality In the Networkmentioning
confidence: 99%